The Role of Flexible Working Arrangements in Improving The Productivity and Well-Being of Female Gen Z Employees in The Hospitality Sector - Wahyu Kusuma Dewi; Nyoman Sri Padmini; Najwa Ghoutsillah; Putri Ratna Dewi (LP2M IAIN Palopo, 2025)
The implementation of Flexible Working Arrangements (FWA) is becoming increasingly important in the hospitality industry as Generation Z members, who have a strong preference for work flexibility and work-life balance, increase their participation. For female Gen Z employees, the challenges of shift-based work, guest service demands, and dual domestic roles make the need for flexibility even more pressing. This study aims to explore the perceptions, experiences, and impacts of Flexible Working Arrangements (FWA) on the productivity and well-being of female Gen Z employees in the hospitality sector. This study used a qualitative approach with a phenomenological design and involved 15 key informants working in five star-rated hotels in Indonesia. Data were triangulated through interviews with direct supervisors and internal document analysis. The results indicate that FWAs have a positive impact on increasing job autonomy, efficiency-based productivity, and emotional well-being of employees. Preliminary findings suggest that FWAs can increase productivity by reducing work fatigue and increasing focus, while also improving the psychological well-being of female employees. However, their effectiveness is strongly influenced by the hotel's operational readiness and leadership patterns. The practical implications of this study emphasize the importance of a structured and gender-sensitive FWA design to improve retention and service quality. The limitations of the study include the limited sample scope and potential perception bias, so further studies with a broader scope are needed.